THE INFLUENCE OF MACROECONOMIC ANNOUNCEMENTS INTO VIETNAMESE STOCK MARKET VOLATILITY - Tran Anh, Minh (My University, 2016)
Market volatility is influenced by many different factors and researchers are discovering and proving impact of those factors in their studies. Macroeconomic announcement is an important factor to market’s volatility, proxied by the famous GARCH model. Inspired by this proven statement, this paper applies the same methodology with the extension of different variables and estimates those factors against the Vietnamese market’s uncertainty. During the observed period of six years, Vietnamese Central Bank governs many monetary policies aiming to stabilise the market and encourage trading. By applying GARCH model, this paper addresses the volatility in Vietnamese market as affected by said announcements. Empirical part of this thesis shows that in general, the market is influenced by U.S.’s significant news announcements, namely CPI and GDP. Otherwise, this study reports that other news announcements from Vietnam and US do not create significant impact into the market. Interestingly, interest rate changing decision has no impact into the said market despite being the commonly influential tool for policy makers to govern the economy.
Keywords: Macroeconomic news announcements; Vietnamese stock market; volatility.; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|